(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ , hChd GdehLhO efg bHd HGH (B( (3GdbGa hGdTjf heG HYOgeG (B) (3HebOGQ hQbJjf (B_ (3bhdg (B: (3aYjd HGdfUH UhJ GdeGA s
(3BNQgG (B:s
(3hBNQg ef HGH (B( (3GdjGA hGdgeRI heGHYOgeG (B) (3bhdg (B: (3dGJdhei hGgLYi GdMeO ddg Je GdLRA GdQGHY ef cJGH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfGhjjf HGdMeQIs
(3Ydi MhGTjgG ebGHdGJ s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs